In depth: The impact of war on Ukrainian science - United Nations Educational, Scientific; Cultural Organization; Gina Doubleday (The UNESCO Courier, 2024)
Conditions for scientific research in Ukraine have greatly deteriorated since the Russian invasion began in February 2022. As a result of the bombing of Ukrainian cities, more than one-third of scientific institutions have been damaged or destroyed and several Ukrainian scientists have been killed. Many researchers and university teachers have been internally displaced, with one in three now having to work remotely. The budget allocated to scientific work has shrunk, leading to cuts in staff salaries, part-time work and suspension of employment. Productivity in science has suffered as a consequence.